2020
DOI: 10.1183/13993003.00453-2020
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophils predict inhaled fluticasone response in bronchiectasis

Abstract: Take home message6-month treatment with inhaled fluticasone propionate significantly improved QoL in bronchiectasis patients who show a blood eosinophil counts ≥3%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 10 publications
0
35
1
1
Order By: Relevance
“…Symptom reduction using ICS has reported by one study by Martinez-Garcia and colleagues, 26 with reduced dyspnoea scores, sputum production and improved QoLperhaps dependent on eosinophil airway inflammation. 27 In the present study, and in contrast to previous neutral studies, 26,28 we have demonstrated increased prevalence of moderate and severe exacerbations in patients with BE using ICS, perhaps due to the study design with standardof-care of the present study.…”
Section: Bronchodilator and Inhaled Corticosteroid Treatment Of Bronchiectasiscontrasting
confidence: 87%
“…Symptom reduction using ICS has reported by one study by Martinez-Garcia and colleagues, 26 with reduced dyspnoea scores, sputum production and improved QoLperhaps dependent on eosinophil airway inflammation. 27 In the present study, and in contrast to previous neutral studies, 26,28 we have demonstrated increased prevalence of moderate and severe exacerbations in patients with BE using ICS, perhaps due to the study design with standardof-care of the present study.…”
Section: Bronchodilator and Inhaled Corticosteroid Treatment Of Bronchiectasiscontrasting
confidence: 87%
“…A decrease in the number of lymphocytes may also participate in the pathogenesis of bronchiectasis, as these cells play a major role in the host adaptive immune response [15]. Other inflammatory cell types such as eosinophils may also play a role in the prognosis and in the response to treatment in these patients [16][17][18][19]. For instance, non-CF bronchiectasis patients with high levels of blood eosinophils were shown to respond better to treatments with different biological agents [20,21] and to inhaled corticosteroids [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Other inflammatory cell types such as eosinophils may also play a role in the prognosis and in the response to treatment in these patients [16][17][18][19]. For instance, non-CF bronchiectasis patients with high levels of blood eosinophils were shown to respond better to treatments with different biological agents [20,21] and to inhaled corticosteroids [17,22]. Similarly, patients with COPD exhibiting blood eosinophil counts lower than 2% were also those showing an inadequate response to inhaled corticosteroids [23].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)-4, IL-5, and IL-13 mediate the T2 inflammatory cascade but are not routinely evaluated [4]. Eosinophil counts in the peripheral blood and oral fractional exhaled nitric oxide (FeNO) are surrogates of the airway eosinophilic inflammation and of the T2-high endotype [5]. Monoclonal antibodies (e.g., mepolizumab and benralizumab, which block IL-5 and IL-5 receptor -IL5ra-, respectively) can reduce the exacerbation rate and improve the quality of life and are able to spare systemic corticosteroid in eosinophilic severe asthmatic patients with bronchiectasis [6].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of FeNO in bronchiectasis are associated with blood eosinophilia, IL13-driven inflammation, and reduced lung function [7,8]. Furthermore, the level of blood eosinophils seems to identify the subgroup of bronchiectasis patients who can be effectively treated by inhaled corticosteroids (ICS) [5,9,10]. Finally, anti-IL5 or anti-IL5ra drugs result in successful outcomes in severe eosinophilic asthmatic patients with concomitant bronchiectasis [6,11].…”
Section: Introductionmentioning
confidence: 99%